World shocks, world prices, and business cycles: An empirical investigation - Andrés Fernández Díaz; Stephanie Schmitt-Grohé; Martín Uribe (Inter-American Development Bank (IDB), 2017)
SVAR models that include a single world price (such as the terms-of-trade) predict that world shocks explain a small fraction of movements in domestic output (typically less than 10 percent). This paper presents an empirical framework in which multiple commodity prices transmit world disturbances. Estimates on a panel of 138 countries over the period 1960-2015 indicate that world shocks explain on average 33 percent of output fluctuations in individual economies. This figure doubles when the model is estimated on post-2000 data. The findings reported here suggest that one-world-price specifications significantly underestimate the importance of world shocks for domestic business cycles.
Keywords: F41; 330; World shocks; Commodity prices; Business cycles; Rohstoffpreis; Zins; Schock; Internationale Konjunktur; Konjunkturzusammenhang; Schätzung; Welt